ChemInform Abstract: Hydrogenous Zintl Phase Ba3Si4Hx (x = 1—2): Transforming Si4 "Butterfly" Anions into Tetrahedral Moieties. Issue 15 (April 2015) - Kranak, Verina F.; Benson, Daryn E.; Wollmann, Lukas; Mesgar, Milad; Shafeie, Samrand; Grins, Jekabs; Haeussermann, Ulrich
Abstract Ba3Si4Hx (x = 1‐2) is prepared by pressurized sintering of the Si46‐ butterfly‐shaped polyanions containing Zintl phase Ba3Si4 in H2 (corundum crucible in an autoclave, 10 bar H2 (20 bar D2), 300 °C, 40 h).